2001
DOI: 10.1007/bf02981909
|View full text |Cite
|
Sign up to set email alerts
|

Morphological diagnoses of the Japan Adult Leukemia Study Group acute myeloid leukemia protocols: Central review

Abstract: A morphological review system of the Japan Adult Leukemia Study Group has developed from the AML-87 through the AML-92 experience. We reviewed 1427 (90%) of 1592 cases enrolled in the AML-87, -89, or -92 protocols for morphology; 1408 (88%) were eligible. The rate of diagnostic concordance between each institute and the Committee on Morphological Diagnosis ranged from 76% to 80%. Acute myeloid leukemia (AML) subtypes were as follows: AML M0, 27 (2%); M1, 179 (13%); M2, 472 (34%); M3, 358 (25%); M4, 265 (19%); … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 35 publications
1
11
1
Order By: Relevance
“…Table 2 shows comparison of AML subtypes with our study. As we look into the frequency of FAB types in different age groups, it was noted that AML-M3 subtype though common below 50 years of age, not a single case of M3 was seen in patients older than 50 years, the finding comparable with a study done in Japan on elderly patients of Acute Myeloid Leukemia [18]. In Acute myeloid leukemia extramedullary infiltration by leukemic cells may cause lymphadenopathy, splenomegaly or hepatomegaly.…”
Section: Citationsupporting
confidence: 68%
See 1 more Smart Citation
“…Table 2 shows comparison of AML subtypes with our study. As we look into the frequency of FAB types in different age groups, it was noted that AML-M3 subtype though common below 50 years of age, not a single case of M3 was seen in patients older than 50 years, the finding comparable with a study done in Japan on elderly patients of Acute Myeloid Leukemia [18]. In Acute myeloid leukemia extramedullary infiltration by leukemic cells may cause lymphadenopathy, splenomegaly or hepatomegaly.…”
Section: Citationsupporting
confidence: 68%
“…The FAB classification has been the major system used by hematologists for more than 20 years. This classification is best suited for places where sophisticated investigations like cytogenetic studies and molecular studies are not available [18]. In our study most common subtype was AML-M1 followed by equal number of M3 and M4.…”
Section: Citationmentioning
confidence: 70%
“…It is very interesting that AML cases with favorable karyotypes such as t(15;17), t(8;21) and inv (16) usually have a high percentage of MPO-positive blasts. 20,21 Recently, a polymorphism in the promoter region of the MPO gene was shown to relate to survival of breast cancer patients after chemotherapy: 22 patients having lower transcriptional activity of MPO (G to A conversion at the 脌463 nucleotide of the MPO gene) showed significantly worse prognosis. The authors of this report concluded, in concordance with our current observation, that the oxidative stress would modify prognosis after chemotherapy for breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12][13] The ECOG study showed that patients with less than Blast MPO Positivity Predicts AML Prognosis T Matsuo et al 50% MPO-positive blasts showed a low CR rate (52.6%), while patients with more than 50% MPO-positive blasts had a significantly better CR rate (85.3%) in the AML M1 subtype (P 录 0.003).…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7][8][9] Thus, the percentage of MPO-positive blast cells has generally been considered to be very important for the diagnosis but not for the prognosis of AML, although a few studies have previously shown the prognostic significance of MPO in AML. [10][11][12][13] Other than the clinical features such as age or performance status, karyotypes of leukemia cells are considered as the most important and independent prognostic factor for AML. The importance of cytogenetics was clearly shown in a previous MRC report, 14 indicating that t(8;21), t (15;17), and inv(16) predicted a favorable outcome and complex karyotype, 脌5, del(5q), 脌7, and abnormalities of 3q defined an adverse group with poor prognosis.…”
Section: Introductionmentioning
confidence: 99%